Quality and usability of information available to patients in the internet on laparoscopic cholecystectomy. - De zoysa, M.I.M.; Pathirage, S.N.; Piyaratne, H.S.B. (My University, 2012)
Laparoscopic cholecystectomy is a commonly performed minimal invasive surgery. Patients' usage of internet to find information on surgery and related issues is increasing. Aim of this study is to review information available to public on internet about laparoscopic cholecystectomy.